The effect of altered caloric and protein intake on the nitrogen balance of swimmers in heavy training
The amount of calories and protein a swimmer receives over a season will contribute to overall performance and success. In heavy training, protein intake should exceed 1.6 grams per kg of body weight per day, an amount, that is at least twice the daily recommended dietary allowance. The value of protein is that it prevents muscle breakdown. A positive nitrogen balance can be maintained when the amount of protein and calories is sufficient to meet the demands of training. Implications: Attention must be paid to the quality and amount of protein contained in a swimmer's diet. In growing athletes, this is particularly important because the amount can be even higher than that found in this study (up to 2 gm/kgBW/day is not uncommon). The amount of complex carbohydrate calories consumed is important for replenishment of glycogen.